How God Becomes Real: Kindling the Presence of Invisible Others. By T. M. Luhrmann - Kaell, Hillary (Journal of the American Academy of Religion, 2021)
How God Becomes Real is an immensely enjoyable read. Tanya M. Luhrmann, writing with the deft hand of an experienced anthropologist, elaborates on the arguments she set forth in her celebrated 2012 book, When God Talks Back, and subsequent articles. At the heart of How God Becomes Real is a question: why do people talk about “the gods” as real but then clearly distinguish between the realness of a chair, for example, and an invisible deity?Luhrmann responds that there are, indeed, different kinds of realness. People work hard to make gods real and are often changed in the process, which prompts them to, again, work to keep the gods close. This feedback loop, argues Luhrmann, helps explain the ontological difference between chairs and gods, while also clarifying the process through which relationships with invisible beings endure. From the vantage point of the anthropology of religion, this premise makes intuitive sense. Guided by scholarship by Robert Orsi, Simon Coleman, Saba Mahmood, and Birgit Meyer, among others, I came to much the same conclusion in my work on how American Christians make “the global” real. Where I found Luhrmann’s work instructive and exciting is in its interdisciplinary sources of inspiration. Although she does draw on (most of) the scholars I just noted, who will be familiar to anthropologists of religion, she also engages cognitive anthropology and psychology.